Recovery of a hypolipidemic polysaccharide from artificially cultivated Sanghuangporus vaninii with an effective method - Zhang, Zuo-fa; Song, Ting-ting; Chen, Jian-fei; Lv, Guo-ying (Frontiers in Nutrition, 2023)
In this study, an effective method was developed to extract the polysaccharide from Sanghuangporus vaninii (PFSV) by destroying the cell wall. Box-Behnken design was employed to determine the optimal processing conditions as follows: processing temperature (80 oC), processing time (0.81 h) and amount of HCl (1.5 mL). Under these conditions, the yield of PFSV reached 5.94±0.16%. The purified polysaccharide (PFSV-2) was found to be a hetero-polysaccharide with an average molecular weight of 20.377 kDa. The backbone of PFSV-2 was composed of an →6)-α-Galp(1→,→2,6)-β-Manp(1→ and →2)-α-Fucp(1→ and was branched of t-α-Manp(1→at position 2 of residue B. PFSV-2 showed hypolipidemic activity by decreasing lipid accumulation and the levels of total cholesterol and triglycerides in zebrafish larvae. Furthermore, PFSV-2 downregulated the pparg, fasn and HMGCRb genes and upregulated the pparab and acaca genes. These findings suggested PFSV-2 may be a promising candidate in lipid regulation therapy.